PENGARUH PERPUTARAN KAS, PERPUTARAN PIUTANG DAN PERPUTARAN PERSEDIAAN TERHADAP PROFITABILITAS DENGAN LIKUIDITAS SEBAGAI VARIABEL INTERVENING PADA BADAN USAHA MILIK DAERAH DAN BADAN LAYANAN UMUM DAERAH KABUPATEN GRESIK - jurnalmap map (Program Pascasarjana Universitas Wijaya Putra Surabaya, 2022)
This study aims to determine: accounts receivable turnover and inventory turnover on profitability with liquidity as an intervening variable in Regional Owned Enterprises and Regional Public Service Agencies of Gresik Regency. The data used is secondary data by means of documentation, both financial reports and profiles of Regional Owned Enterprises and Regional Public Service Agencies in Gresik Regency. Data processing using path analysis. The results showed that cash turnover had no effect on liquidity. Accounts receivable turnover has an effect on liquidity. Inventory turnover has no effect on liquidity. Cash turnover has an effect on profitability. Accounts receivable turnover has an effect on profitability. Inventory turnover has an effect on profitability. Liquidity has no effect on profitability. Cash turnover has no significant effect through liquidity. Accounts receivable turnover has no significant effect through liquidity. Inventory turnover has no significant effect through liquidity.